Terminal deoxynucleotidyl transferase activity in childhood and adult acute lymphoblastic leukaemia. Issue 8 (August 1981) - Proctor, S J; Dickinson, A M; Fail, B; Walker, W; Serisier, S
Abstract : The measurement of terminal deoxynucleotidyl transferase (TDT) activity in leukaemic blasts of 26 cases of acute lymphoblastic leukaemia (ALL) (13 children less than 14 years, 13 adults greater than 14 years) demonstrated significantly greater activities of the enzyme on a proportion of the adults. The predominant cytological sub-type in the adult patients was L2 (FAB classification) whereas L1 cytological sub-type dominated in the childhood group. There was no relation between TDT values and FAB sub-type but the highest activities in the childhood group were seen in patients assessed at the time of relapse. We conclude that continued use of quantitative TDT estimations may provide useful information in further characterising the currently recognised cytological and immunological sub-types in ALL.